Physical Activity Counseling by Diabetes Educators Delivering Diabetes Self-management Education and Support. (October 2016) - Powell, Robert O.; Siminerio, Linda; Kriska, Andrea; Rickman, Amy; Jakicic, John M.
Purpose: The purpose of this study was to examine factors that influence physical activity counseling of diabetes educators delivering diabetes self-management/support (DSME/S). Methods: Diabetes educators were surveyed about their DSME/S counseling at the American Association of Diabetes Educators Pennsylvania State Diabetes Conference to explore (1) time dedicated to physical activity counseling, (2) importance placed on physical activity as a treatment for diabetes, (3) knowledge of the 2008 Physical Activity Guidelines for Americans, (4) level of confidence with physical activity counseling, and (5) barriers associated with physical activity counseling. Results: A sample of 119 diabetes educators with 13.0 ± 8.6 years of DSME/S experience participated in the survey (95.8% female; 94.1% white; 60.5% nurses; 73.9% Certified Diabetes Educators). Of 4 common DSME/S content areas (healthy eating, taking medications, monitoring blood glucose, and physical activity), physical activity was ranked as the third most important behind healthy eating and taking medications, with 14.5 ± 12.1 minutes per session spent counseling on physical activity. The proportion of educators acknowledging the current physical activity guidelines for moderate-intensity aerobic activity, vigorous-intensity aerobic activity, and resistance training was 74%, 20.5%, and 62.8%, respectively. Being "very confident" for counseling on physical activity was reported by 54.7%, while "inability to engage patients in physical activity" and "time allotted for DSME/S visits" were the most challenging personal and practice barriers reported, respectively. Physical activity is an important lifestyle behavior for the treatment of diabetes. Conclusions: Findings suggest that there are challenges to physical activity counseling within DSME/S. Strategies to improve physical activity counseling by diabetes educators warrant attention.